Adultry, Fornication, and Rape Cases: The Divergent Views of the Four Schools of Jurisprudence - Abdullahi, Ja’afar Agaji (South Asian Journal of Social Sciences and Humanities, 2021)
Man was created by Almighty Allah as Khalifatullah on terrain so that he might animates and decree on it. This tenacity cannot be grasped unless the humankinds preserve itself, incarnates, flourishes, humanizes, and worships its creator. Consequent upon that the Creator has positioned some desires and instincts in man so that he might be encouraged towards several undertakings which assures the survival of the classes. It is in line with the above, that this paper attempts to examine the concept of adultery, fornication and rape, as well as the divergent opinions of the four schools of jurisprudence among others. Thus, the paper concludes that Islam categorically urges the faithful to distant themselves not even from adultery, fornication and rape, but any lewdness. In addition, Islam battled with the above vices for they lead to confusion of linage, child-abuse, breaking up of families, bitterness in relationship, and spread of disease, and laxity in morals. Thereupon, the paper recommends among other things that believers should be conscious of their Lord and distant themselves from committing the afore-mentioned indecencies. And when the malfactor is before the law, he should be punished without any fear, prejudice or mercy.
Keywords: Adultery; Fornication; Rape; Divergent Views; Four Schools of Jurisprudence